Enhancement the Properties of Construction Urea Composition with Polymer Additive - Arslanov Islom Kimsanovich (International Journal of Community Service & Engagement, 2021)
This scientific article provides physicochemical studies where the addition of a gel polymer has a positive effect on the process of structure formation. The presence of chemical bonds between the components, a change in the morphology of the structure, a decrease in microporosity, an increase in the density and thermal stability of the urea composition are shown. Polymer composite materials are used as chemically resistant coatings, polymer mortars and polymer concretes. Along with such valuable properties as incombustibility, colorlessness, good miscibility with water, etc., urea resins and compositions based on them have a number of disadvantages. The object of the study is a carbamide composition with a quartz filler and an addition of a gel polymer, its structure formation and chemical resistance. The methodological basis of the study is the polystructural theory of composite building materials (CBM) and the modeling of the study of the chemical resistance of the urea composition in aggressive conditions. The issues of finding effective water-binding additives and studying their effect on structure formation, properties and technology of urea compositions remain relevant and require additional research. It is shown that with the optimal content of the gel-polymer additive in the composition of 0.13% of the filler weight, the compressive strength and specific impact strength increase by 17; 13% and shrinkage is reduced by 7%. It was found that due to the enhancement of the adhesive bond between the components and the improvement of the pore structure under the action of the gel-polymer additive, the chemical resistance of the urea composition with quartz filler increases. So, water, acid and alkali resistance are 0.75; 0.80 and 0.85 and which, respectively, are 6, 7 and 7 points higher than the reference composition.